A guide to cancer genetics in clinical practice - Clark, Sue (Tfm Pub., 2009)
Covers the basic concepts of cancer genetics. This book deals with the common inherited cancer syndromes. It aims to facilitate identification of high-risk individuals and families, to inform interaction with geneticists and other sub-specialists, to provide a basis for patient management and to stimulate interest in these conditions.